Embodied sharpness: exploring the slicing gesture in political talk shows - Ladewig, Silva H. (Frontiers in Psychology, 2025)
This paper explores the Slicing gesture within German political talk shows, focusing on its role in recurrent gesture sequences observed in German political talk shows. Through a detailed historical overview of recurrent gestures in political communication and an extension of the repertoire of recurrent gestures in German speakers, the study emphasizes the Slicing gesture’s function in stance-taking and self-presentation. Highlighting its forms and functions, the analysis demonstrates how this gesture enacts sharpness, decisiveness, and clarity. The study integrates embodied and phenomenological perspectives, showing how kinesthetic experiences shape the gesture’s meaning and metapragmatic dimensions. By contributing to the understanding of recurrent gestures as multimodal resources in political discourse, the paper sheds light on the interplay between embodied communication and rhetorical style.